A rare case of unilateral parotid gland agenesis - Kiarash Soltani, MD; Mahdi Taghdiri, MD; Elham Keshavarz, MD; Pourya Kanani, MD (Radiology Case Reports, 2025)
Parotid gland agenesis is a rare congenital anomaly with fewer than 30 cases reported in the literature. It can present with xerostomia, facial asymmetry, recurrent infections, or may be entirely asymptomatic. Due to its rarity and potential to mimic other pathological conditions, especially in cases of facial asymmetry, awareness is crucial for accurate diagnosis. We report the case of a 39-year-old man referred to our clinic for routine follow-up of a thyroid nodule. The patient had no history of systemic illness or symptoms related to salivary gland dysfunction. During neck ultrasonography, an unusual asymmetry was observed, raising suspicion for unilateral parotid gland absence. Subsequent MRI of the head and neck confirmed complete agenesis of the right parotid gland. Clinical examination and detailed history revealed no signs of xerostomia, facial asymmetry, recurrent infections, or associated syndromic features. This case represents an incidental finding of isolated unilateral parotid gland agenesis in an asymptomatic adult. The embryological basis likely involves disruptions in the development of the first and second branchial arches. Imaging, particularly MRI, plays a key role in confirming the diagnosis and differentiating agenesis from more concerning and common conditions such as neoplasms or acquired atrophy. Isolated unilateral parotid gland agenesis can remain clinically silent and be discovered incidentally. Awareness of this rare anomaly is important to avoid misdiagnosis and unnecessary interventions. In asymptomatic individuals, no treatment is required, though monitoring and patient education are recommended.